DECISION SUPPORT SYSTEM PENENTUAN KELAYAKAN PENERIMA PINJAMAN KREDIT DENGAN METODE FUZZY MULTI CRITERIA DECISION MAKING (STUDI KASUS : KOPERASI BUNGA MAWAR KABUPATEN KERINCI JAMBI) - Novhirtamely Kahar; Reny Wahyuning Astuti; Irfani Kurnia Perdana (JURNAL AKADEMIKA)
Micro, Small and Medium Enterprises (MSME) play an important role in economic development because labor absorption rate is relatively high and needs little capital investment. Therefore, President Susilo Bambang Yudhoyono inaugurated the MSME credit underwriting pattern with the name People's Business Credit and supported by Presidential Instruction No. 5 of 2008 on the 2008-2009 Economic Focus Program to ensure the implementation or acceleration of the implementation of these small loans. Koperasi Bunga Mawar in determining the loan eligibility of beneficiaries is closely related to decision making that involves a lot of criteria. This study aims to develop a system that can support decision making for credit loan recipients in Koperasi Bunga Mawar with Fuzzy Multi Criteria Decision Making (FMCDM), so that the resulting decision in accordance with the criteria of a predetermined and well-deserved recipient of the loan is given credit. The system is built using the programming language Delphi 7.0 with the input data are the data of potential borrowers, criteria, rating interests, and suitability rating, and the output are the information on the calculation and the best candidates for loan recipients. Decision making based on criteria as a condition that has been determined by the cooperative. With the construction of this system is expected to facilitate and accelerate the Koperasi Bunga Mawar in the decision-making process and eligible members are entitled to receive a credit loan.